Features of economic sectors development in mountain territories of the Republic of Dagestan - A. M. Esetova; I. K. Kerimov (Вестник университета)
The peculiarities of development of various branches of economy in the mountain territories of the Republic of Dagestan have been considered. Geographical, climatic, and socio-economic conditions of these areas have a significant impact on their development. The current state of economic sectors in the mountain territories of the Republic of Dagestan has been analyzed. Special attention has been paid to the factors affecting economic development of the region such as lack or high degree of wear and tear of infrastructure, insufficiency of both public and private investment, as well as lack of personnel. Promising sectors of the mountain zone of the constituent entity have been identified such as agriculture, industry, tourism, and folk arts and crafts. Recommendations have been given on increasing economic activity efficiency and improving investment climate in the mountain territories of the region, aimed at ensuring sustainable development and improving the standard of living of the local population. The article concludes that it is necessary to solve a number of problems that hinder development of mountain territories of the Republic of Dagestan. In particular, it is worth implementing measures aimed at deve loping infrastructure, attracting extra-budgetary investments, training qualified personnel, promoting tourism opportunities, and expanding measures of state support for business activities in the mountain territories.